A new approach to efficient and safe gas production from unsealed marine hydrate deposits. (15th January 2021) - Sun, Yi-Fei; Zhong, Jin-Rong; Chen, Guang-Jin; Cao, Bo-Jian; Li, Rui; Chen, Dao-Yi
Highlights: A highly simulated unsealed marine hydrate deposits is established. The technology of pressure-retaining gas injection is proposed and proved. The pre-depressurization operation can significantly enhance gas recovery. An optimized strategy for hydrate exploitation is proposed. Abstract: The exploitation of unsealed marine hydrate deposits is of greater commercial value, but also more challenging because of the risks of the invading of huge body of sea water and subsidence of the seabed. In this work, we proposed a new method to recover natural gas from the usealed hydrate deposits saturated with water by pressure-retaining gas (CO2  + H2 ) injection. A series of experimental simulations was performed to prove its feasibility through establishing a highly simulated unsealed marine hydrate-bearing sediments system. The results demonstrated that overlying water invading was almost completely inhibited for the pressure-retaining approach while unimpeded for the simple depressrization process. Further, we designed a temporary depressurization process before gas injection to establish a flow field for gas in the sediments. This combined operation effectively enhanced the migration and spread of the injected gas, eventually increasing gas recovery ratio from 25% to 60% while the produced water/gas ratio remains as low as 12.6 ST kg/m 3 . Additionally, it is proved that the balance between CO2 sequestered and CH4 recovered could be achieved, which was an excellent support for reservoir stability. The combination method realized a higher CH4 concentration in the produced gas and a lower injection-production ratio, which greatly reduced the costs of gas injection and subsequent treatment of produced gas. For comparison, similar simulation work was also performed with respect to sealed gas-rich hydrate-bearing sediments. Overall, this temporary depressurization aided pressure-retaining gas injection approach is very promising for high efficient and safe exploitation of marine hydrtates.